1997
DOI: 10.1172/jci119131
|View full text |Cite
|
Sign up to set email alerts
|

Tetrahydrobiopterin restores endothelial function in hypercholesterolemia.

Abstract: In hypercholesterolemia, impaired nitric oxide activity has been associated with increased nitric oxide degradation by oxygen radicals. Deficiency of tetrahydrobiopterin, an essential cofactor of nitric oxide synthase, causes both impaired nitric oxide activity and increased oxygen radical formation. In this study we tested whether tetrahydrobiopterin deficiency contributes to the decreased nitric oxide activity observed in hypercholesterolemic patients. Therefore, L -mono-methylarginine to inhibit basal nitri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
354
4
10

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 554 publications
(393 citation statements)
references
References 50 publications
25
354
4
10
Order By: Relevance
“…Administration of BH 4 , at a concentration which has been demonstrated to enhance production of NO and restore endothelial function (Cosentino & Katusic 1995;Tiefenbacher et al, 1996;Pieper, 1997), resulted in a slight enhancement but not normalization of endothelial function. This ®nding suggests that the dysfunction of the endothelium at least in part was due to lack of the co-factor BH 4 , which is in accordance with observations in patients with hypercholesterolemia (Stroes et al, 1997). When the vessels were preincubated with a combination of L-arginine and BH 4 , the endothelial function of E8xLDLR8 mice was markedly enhanced and not di erent from that observed in vessels from control mice.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Administration of BH 4 , at a concentration which has been demonstrated to enhance production of NO and restore endothelial function (Cosentino & Katusic 1995;Tiefenbacher et al, 1996;Pieper, 1997), resulted in a slight enhancement but not normalization of endothelial function. This ®nding suggests that the dysfunction of the endothelium at least in part was due to lack of the co-factor BH 4 , which is in accordance with observations in patients with hypercholesterolemia (Stroes et al, 1997). When the vessels were preincubated with a combination of L-arginine and BH 4 , the endothelial function of E8xLDLR8 mice was markedly enhanced and not di erent from that observed in vessels from control mice.…”
Section: Discussionsupporting
confidence: 89%
“…Tetrahydrobiopterin (BH 4 ) is a co-factor for NO synthase in the production of NO from L-arginine (Cosentino & LuÈ scher, 1998;Marletta et al, 1998;Werner et al, 1998). Administration of BH 4 has been demonstrated to enhance NO production in prehypertensive rats (Cosentino & LuÈ scher, 1998) and to restore endothelium-dependent vasodilation in isolated coronary arteries following reperfusion injury (Tiefenbacher et al, British Journal of Pharmacology (2000) 131, 1255 ± 1261 ã 2000 Macmillan Publishers Ltd All rights reserved 0007 ± 1188/00 $15.00 www.nature.com/bjp *Author for correspondence; E-mail: john.pernow@ks.se 1996) and in patients with hypercolesterolemia (Stroes et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has been demonstrated that supplementation of BH 4 or folic acid improves endothelial function in smokers, in patients with diabetes, hypertension, hypercholesterolemia and chronic heart failure and in elderly subjects. [76][77][78][79][80][81][82] Co-infusion of BH 4 resulted in a significant increase in acetylcholine-induced vasodilation in healthy men. 78 Aging was found to be significantly correlated with acetylcholineinduced vasodilation, urinary 8-OHdG, serum MDA-LDL and change in acetylcholine-induced vasodilation after co-infusion of BH 4 .…”
Section: Tetrahydrobiopterin (Bh 4 )mentioning
confidence: 99%
“…Insufficiency of BH 4 or its oxidation to dihydrobiopterin by peroxynitrite or other oxidants leads to uncoupling of eNOS that promotes generation of superoxide instead of NO. 21 Thus, a deficiency of BH 4 produces two additive physiologic consequences: (a) uncoupling of the L-arginine NO pathway resulting in increased formation of oxygen-free radicals by eNOS 22 and (b) loss of NO production. 23 In a recent study, we found that deoxycorticosterone acetate salt hypertension caused BH 4 oxidation in aortas of mice, leading to a marked increase in superoxide production and a significant reduction in NO production.…”
Section: Potential Mechanismsmentioning
confidence: 99%